Pengaruh Pemberian Tepung Indigofera Sebagai Pengganti Bungkil Kedelai Dan Dedak Dalam Ransum Terhadap Performa Produksi Entog (Cairina Moschata) - Ali Nasyeh; Dini Widianingrum; Rachmat Somanjaya (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
This research was conducted in March - August 2021, located in Darma District, Kuningan Regency, West Java Province, Indonesia, which is located at the coordinates 7°02°09.4